2012
DOI: 10.1111/j.1834-7819.2011.01663.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of cone beam computed tomography for assessment of the temporomandibular joints

Abstract: Radiographic examination is essential for the diagnosis and management of temporomandibular joint (TMJ) disorders. The goals of TMJ radiography are to evaluate cortical and trabecular architecture of the bony structures and confirm their integrity, to assess the extent and monitor progression of osseous changes, and to evaluate the response to treatment. Accurate evaluation of the TMJ by conventional radiography is limited by structure superimposition. Cone beam computed tomography (CBCT) provides high-resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
149
0
19

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(170 citation statements)
references
References 48 publications
(50 reference statements)
2
149
0
19
Order By: Relevance
“…CBCT has a capability to detect early changes in TMJ osteoarthritis like irregular cortical outlines, erosions, osteophyte formation, subchondral cyst formation, narrowing of joint space, flattening of articular surfaces and sub-chondral sclerosis [32,33]. Similar changes are also found in inflammatory disorders but to a Figure 4A).…”
Section: Temporomandibular Jointssupporting
confidence: 50%
“…CBCT has a capability to detect early changes in TMJ osteoarthritis like irregular cortical outlines, erosions, osteophyte formation, subchondral cyst formation, narrowing of joint space, flattening of articular surfaces and sub-chondral sclerosis [32,33]. Similar changes are also found in inflammatory disorders but to a Figure 4A).…”
Section: Temporomandibular Jointssupporting
confidence: 50%
“…86 In addition, reports of cases have been published, such as synovial chondromatosis, 87,88 fibrous ankylosis in RA 89 and metastasis of a bronchial carcinoma. 90 Similar rare conditions have been illustrated in previously mentioned review articles, 5,6 which also showed trauma and developmental cases. Condylar fractures can be nicely demonstrated with CBCT ( Figure 9) and so can developmental anomalies (Figure 10).…”
Section: Juvenile Idiopathic Arthritismentioning
confidence: 72%
“…4 Available literature on CBCT has become extensive since then, including reviews for application to the TMJ. [5][6][7][8] The present overview will give an update on TMJ imaging using CBCT and its diagnostic value compared with other imaging modalities, with main sections on diagnostic accuracy and OA. The usefulness of CBCT in the diagnostic assessment of other TMJ conditions will be shortly reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…CBCT provides high-resolution multiplanar images and emits a significantly lower radiation dose compared with CT. CBCT machines are less bulky and available in the community, whereas multiplanar CT is only available in a hospital environment. CT provides accurate hard tissue information but poor soft tissue visualisation [6].…”
Section: Diagnostic Methodsmentioning
confidence: 99%